Stability of bacteriocin-like inhibitory substance (BLIS) produced by Pediococcus acidilactici kp10 at different extreme condition - Md Sidek, Nurul Lyana; Halim, Murni; Tan, Joo Shun; Abbasiliasi, Sahar; Mustafa, Shuhaimi; Ariff, Arbakariya (Hindawi, 2018)
Nowadays, bacteriocin industry has substantially grown replacing the role of chemical preservatives in enhancing shelf-life and safety of food. The progress in bacteriocin study has been supported by the emerging of consumer demand on the applications of natural food preservatives. Since food is a complex ecosystem, the characteristics of bacteriocin determine the effectiveness of their incorporation into the food products. Among four commercial media (M17 broth, MRS broth, tryptic soy broth, and nutrient broth) tested, the highest growth of Pediococcus acidilactici kp10 and bacteriocin-like-inhibitory substance (BLIS) production were obtained in the cultivation with M17. BLIS production was found to be a growth associated process where the production was increased concomitantly with the growth of producing strain, P. acidilactici kp10. The antimicrobial property of BLIS against three indicator microorganisms (Listeria monocytogenes, Escherichia coli, and Staphylococcus aureus) remained stable upon heating at 100°C but not detectable at 121°C. The BLIS activity was also observed to be stable and active at a wide pH range (pH 2 to pH 7). The BLIS activity remained constant at -20°C and -80°C for 1 month of storage. However, the activity dropped after 3 and 6 months of storage at 4°C, -20°C, and -80°C with more than 80% reduction. The ability of bacteriocin from P. acidilactici kp10 to inhibit food-borne pathogens while remaining stable and active at extreme pH and temperature is of potential interest for future applications in food preservatives.